2011
DOI: 10.1016/j.drugalcdep.2010.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and drug use factors associated with HIV-1 recombinants and dual infections in Northern Thai drug users: Associations of risk with genetic complexity

Abstract: b s t r a c tBackground: Dual infection with diverse HIV strains can foster the emergence of recombinants. The resulting increase in viral genetic diversity is a major challenge for vaccine development HIV treatment. In this study we aim to investigate the socio demographic factors associated with an increasing level of genetic diversity among HIV strains in a population of drug-users in Northern Thailand. Methods: From 1999 through 2000, 2231 volunteers were enrolled in the Opiate-Users Research in Chiang Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
3
0
2
Order By: Relevance
“…They assume that the burden of responsibility will make him quit the abused substance that may be reason why most of the drug abusers are married. Education wise our results agree with previous finding of different researches that most of the drug abusers are illiterate or low educated 16,17,18,19,20,21 . It presents an interesting story to interpret.…”
Section: Discussionsupporting
confidence: 92%
“…They assume that the burden of responsibility will make him quit the abused substance that may be reason why most of the drug abusers are married. Education wise our results agree with previous finding of different researches that most of the drug abusers are illiterate or low educated 16,17,18,19,20,21 . It presents an interesting story to interpret.…”
Section: Discussionsupporting
confidence: 92%
“…The information retrieved from RV148 volunteers included basic sociodemographic characteristics, but the volunteers were not asked questions regarding behaviors that may increase the risk for HIV acquisition (41). In cohorts in Thailand and worldwide, it has been shown that there were associations between the complexity of HIV-1 strains and sociodemographic characteristics and behaviors that may increase the risk of HIV infection (e.g., more frequent needle sharing among IDUs [61], the presence of sexually transmitted infections [63], exchanging sex for money [65,66), and having high numbers of sex partners [66]). We compared the frequency of different molecular forms-pure subtypes and recombinants-between RV148 and other low-risk cohorts (i.e., RV109, a mother-to-child transmission [MTCT] [83]) from Thailand that have also been genotyped using MHAbce.…”
Section: Discussionmentioning
confidence: 99%
“…Serum viral RNA was extracted using a QIAamp Viral RNA Mini Kit (Qiagen, Hilden, Germany). Subtype distributions using MHA genotyping, demographic characteristics and risk factors of this study population were described elsewhere (Kijak et al, 2011).…”
Section: Methodsmentioning
confidence: 99%